Uncovering Latent Deficits Due to Mild Traumatic Brain Injury by Using Normobaric Hypoxia Stress - Temme, Leonard; Bleiberg, Joseph; Reeves, Dennis; Still, David L.; Levinson, Dan; Browning, Rebecca (Frontiers in Neurology, 2013)
Memory deficits and other cognitive symptoms frequently associated with mTBI are commonly thought to resolve within 7 to 10 days. This generalization is based principally on observations made in individuals who are in the unstressed environmental conditions typical to a clinic and so does not consider the impact of physiologic, environmental or psychological stress. Normobaric Hypoxia (NH) stress can be generated by mixing normal mean sea level air (MSL) containing 21% oxygen (O2) with nitrogen, which is biologically inert, so that the resultant mixed gas has a partial pressure of O2 approximating that of specified altitudes. This technique was used to generate NH equivalents of 8,000, 12,000 and 14,000 feet above MSL in a group of 36 volunteers with an mTBI history and an equal number of controls matched on the basis of age, gender, weight, etc. Short term visual memory was tested using Matching to Sample (M2S) subtest of the BrainCheckers analogue of the Automated Neuropsychological Assessment Metrics (ANAM). Although there were no significant differences in M2S performance between the two groups of subjects at MSL, with increased altitude, performance deteriorated in the mTBI group as predicted to be significantly worse than that of the controls. When the subjects were returned to MSL, the difference disappeared. This finding suggests that the “hypoxic challenge” paradigm developed here has potential clinical utility for assessing the effects of mTBI in individuals who appear asymptomatic under normal conditions.